If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -5 = 9y + 10 Reorder the terms: -5 + 7y = 9y + 10 Reorder the terms: -5 + 7y = 10 + 9y Solving -5 + 7y = 10 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -5 + 7y + -9y = 10 + 9y + -9y Combine like terms: 7y + -9y = -2y -5 + -2y = 10 + 9y + -9y Combine like terms: 9y + -9y = 0 -5 + -2y = 10 + 0 -5 + -2y = 10 Add '5' to each side of the equation. -5 + 5 + -2y = 10 + 5 Combine like terms: -5 + 5 = 0 0 + -2y = 10 + 5 -2y = 10 + 5 Combine like terms: 10 + 5 = 15 -2y = 15 Divide each side by '-2'. y = -7.5 Simplifying y = -7.5
| 5(-2+6n)=110 | | -5(6x+3)=-195 | | (s)(s)(s)(s)= | | 10(k+10)=50 | | -14+n=-24 | | 26=m+7 | | x+.09x=4690 | | x-15=-22 | | x+.09x=4010 | | 9m-4n+3m= | | 5w+2=6w-4 | | 3x+5=5x-5 | | 9m-4n=3m | | x-8=-8x | | 28w-1=29w-2 | | -7(5p+4)-42=5(4p+8) | | x+.09x=3740 | | -10x=290 | | 4t-8t=32 | | 8y+2=3y+8 | | 2-2=5 | | 3+x-2=10 | | 2(-3)(y)(y)(y)(y)(y)= | | x^2-12x+12=0 | | 5f+90=6f+9 | | (14x^3+x^2-3x)+(2x+1)=0 | | x^2-0.67x-2.89=0 | | m^3+5m^2=0 | | x^2-4.7x=2.8 | | 117-90=34y-43y | | -350=-10(-5b) | | 9x^2-54=0 |